Effect of co-vaccination of cattle with RB51 and BCG on vaccine-specific CD4+ T cell responses - Sterle, Haley M.; Putz, Ellie J.; Palmer, Mitchell V.; Olsen, Steven C.; Boggiatto, Paola M. (Frontiers in Immunology, 2025)
IntroductionBrucella abortus and Mycobacterium bovis, the causative agents of bovine brucellosis and tuberculosis respectively, are zoonotic bacterial pathogens that both contribute to major economic losses in the cattle industry and pose a human health risk worldwide. Co-infections of cattle with B. abortus and M. bovis have been identified in various developing countries, necessitating the development of an efficacious strategy for controlling both important zoonotic diseases even in the event of co-infection. Brucella abortus strain RB51, a live attenuated vaccine for bovine brucellosis that is currently used in the US, is highly effective at preventing reproductive failure due to brucellosis in cattle. Bacillus Calmette-Guérin (BCG) is a live attenuated vaccine strain of M. bovis that provides protection against bovine tuberculosis in cattle but is not currently licensed for use in the US.MethodsThe study presented here compares functional Th1 responses of RB51 + BCG vaccinated cattle to responses of RB51-only and BCG-only vaccinated cattle to evaluate the feasibility of a combined vaccination strategy for controlling both bovine brucellosis and tuberculosis.ResultsThis work identified that peripheral blood mononuclear cells (PBMC) from RB51 vaccinates proliferate not only in response to stimulation with killed RB51 but also in response to mycobacterial antigen PPDb. Combination vaccinates show significantly more CD4+ T cell proliferation than single BCG vaccinates when stimulated with PPDb, while no differences were observed between RB51 and combination vaccinates stimulated with RB51.Discussion/conclusionSignificantly enhanced BCG-specific Th1 responses in combination vaccinates compared to BCG-only vaccinates suggest that combining vaccinations for B. abortus and M. bovis may alter the host CD4+ T cell response.